THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON BANK PROFITABILITY - Erdiana, Della; Marcellina, Lola Via; Hwihanus, Hwihanus (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study examines the effect of Corporate Social Responsibility (CSR) on bank profitability in countries such as Nigeria, Vietnam, Indonesia, Pakistan and Kenya. The concept of CSR has evolved from mere corporate philanthropy to an integral part of modern business. Research shows that CSR implementation can add value to the banking sector, such as economic efficiency and increased brand recognition. While some studies show a positive relationship between CSR and bank profitability, there are also findings of negative impacts on some variables such as Net Interest Margin. Recommendations from this study include developing strategies to improve financial performance, increasing CSR investment and disclosure, and the need for clear regulations to govern CSR spending. Further research is needed to analyze the relationship between CSR and firm performance in other economic sectors. This study uses the Literature Review method to analyze the relationship between CSR and bank profitability, focusing on CSR activity disclosure and bank financial performance in Nigeria. The results show that CSR activity disclosure has a positive impact on bank profitability in Nigeria, and recommends increased investment and CSR disclosure as a measure to improve bank financial performance.